Species specificity in the activation of Xer recombination at dif by FtsK. - Yates, J; Aroyo, M; Sherratt, D; Barre, F (2003)
In Escherichia coli, chromosome dimers are resolved to monomers by the addition of a single cross-over at a specific locus on the chromosome, dif. Recombination is performed by two tyrosine recombinases, XerC and XerD, and requires the action of an additional protein, FtsK. We show that Haemophilus influenzae FtsK activates recombination by H. influenzae XerCD at H. influenzae dif. However, it cannot activate recombination by E. coli XerCD. Reciprocally, E. coli FtsK cannot activate recombination by the H. influenzae recombinases at H. influenzae dif. We took advantage of this species specificity to gain further insight into the mechanism of activation of Xer recombination at dif by FtsK. We mapped the region of FtsK implicated in species specificity to the extreme 140-amino-acid C-terminal residues of the protein. Our results suggest that FtsK interacts directly with XerCD in order to activate recombination at dif.